Violence and Social Memory in Twentieth-Century Belfast: Stories of Buck Alec Robinson. (26th August 2014) - O'Connell, Sean
Abstract This article explores the life and commemoration of Buck Alec Robinson. A feared loyalist killer in 1920s Belfast, in more recent times he has featured as a lion-keeping "character" on wall murals and in tourist guide books. Robinson is employed as a case study to investigate two separate but, in this case, interlinked historiographical debates. The first involves Norbert Elias's analysis of the decline of violence. The second relates to discussion of the analysis of social memory in working-class communities, with violence being placed therein. The article supports historical assessments suggesting that the "civilizing offensive" had an uneven impact. That point is usually made in the context of working-class men. This article extends it to political elites in Belfast and probes their flirtations with violent hard men. The case is made that it is a mistake to assume the "civilizing" dynamic is to be understood as a teleological or top-down process.